2016
DOI: 10.1371/journal.ppat.1006104
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Low-Level Replication of SIVΔnef Drives Maturation of Antibody and CD8 T Cell Responses to Induce Protective Immunity against Vaginal SIV Infection

Abstract: Defining the correlates of immune protection conferred by SIVΔnef, the most effective vaccine against SIV challenge, could enable the design of a protective vaccine against HIV infection. Here we provide a comprehensive assessment of immune responses that protect against SIV infection through detailed analyses of cellular and humoral immune responses in the blood and tissues of rhesus macaques vaccinated with SIVΔnef and then vaginally challenged with wild-type SIV. Despite the presence of robust cellular immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
(72 reference statements)
2
19
0
Order By: Relevance
“…In vaccine studies with adult macaques, the avidities of anti-Env serum IgG measured by NaSCN displacement ELISA have been correlated with the levels of ADCC activity (35) and protection against rectal or vaginal SHIV or SIV challenge (30,31,36,37). In the current study, the avidity indices of C.1086 gp120-specific IgG measured in the NaSCN ELISA did not show evidence of differences between groups.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…In vaccine studies with adult macaques, the avidities of anti-Env serum IgG measured by NaSCN displacement ELISA have been correlated with the levels of ADCC activity (35) and protection against rectal or vaginal SHIV or SIV challenge (30,31,36,37). In the current study, the avidity indices of C.1086 gp120-specific IgG measured in the NaSCN ELISA did not show evidence of differences between groups.…”
Section: Discussionmentioning
confidence: 45%
“…We have previously shown that oral vaccine priming followed by systemic boosting in infants generates salivary or intestinal IgA responses that, albeit not protective against infection, correlate with control of viremia after oral SIV exposure (20,29). Similarly, vaccine-mediated induction of Env-specific mucosal IgA responses at sites of SIV or SHIV challenge has been associated with protection, delayed rates of infection, or control of viremia in adult macaques (30,36,37,42). Consistent with the induction of mucosal gp120-specific IgA, gp120-specific B cells in intestinal tissues were only detected in the extended-interval group.…”
Section: Discussionmentioning
confidence: 99%
“…We confirm that CD4 + and CD8 + T cells express memory markers in the FRT (17), whereas naive cells were primarily found in blood and LNs. Among the memory T cells, resident memory lymphocytes have been described in tissues such as the vagina (18). Our analyses performed in one vaccinated animal showed that CD8 + resident memory T cells were primarily present in the vagina (39.8% among effector memory T cells) and in the cervix (22.2% among effector memory T cells) and were less frequent in the uterus (2.5% among effector memory T cells) (data not shown).…”
Section: Discussionmentioning
confidence: 66%
“…Vaccine strategies that promote the establishment of T RM cells within the mucosal tissues hold promise for limiting early dissemination of virus infections such as HIV-1 and Influenza [7, 51]. We demonstrated that CD8 T cells depend on mTORC1 signaling to specifically accumulate with mucosal tissues.…”
Section: Discussionmentioning
confidence: 89%